"Where temporality intersects with eternity." "Italian art in the works of Jarosław Iwaszkiewicz" - Peroń, Małgorzata (Studia Teologiczne Białystok Drohiczyn Łomża, 2023)
Italian art in Jarosław Iwaszkiewicz's work is a source of literary motifs. The creator draws on his rich artistic achievements, making art the subject of poetic description, and also includes it in the world of his prose works. Reflection on its everlasting beauty is, on the one hand, connected with the sense of the insignificance of human fate, and on the other hand, it allows us to ask questions about what transcends man, what is related to the spiritual sphere and the sacred. Importantly, the writer, who has systematically refrained from typically religious topics, chooses religious works as the subject of his analysis and interpretation. Evidence of his fascination with Italy was also recorded in his diaries and essay books. Travels to Italy shaped the writer's aesthetic sense, which pointed to the durability and value of Mediterranean culture. He was particularly interested in the art of the Renaissance and Baroque, in which he discovered universal and timeless themes. They were the source of his creative inspiration.